Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/hbm.23462
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of brain connectivity in obesity

Abstract: Global brain connectivity (GBC) identifies regions of the brain, termed "hubs," which are densely connected and metabolically costly, and have a wide influence on brain function. Since obesity is associated with central and peripheral metabolic dysfunction we sought to determine if GBC is altered in obesity. Two independent fMRI data sets were subjected to GBC analyses. The first data set was acquired while participants (n = 15 healthy weight and 15 obese) tasted milkshake and the second with participants at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 147 publications
(245 reference statements)
11
56
1
Order By: Relevance
“…In our large cohort, we did not observe previously reported increased putamen and insula connectivity [Hogenkamp et al, ], decreased insula–anterior cingulate cortex (ACC) connectivity [Moreno‐Lopez et al, ], increased salience network connectivity [Figley et al, ; Garcia‐Garcia et al, ], reduced temporal lobe network connectivity [Kullmann et al, ] or increased DMN connectivity [Kullmann et al, ; Legget et al, ; Tregellas et al, ] with higher BMI. Similar to our results, one study reported reduced precuneus connectivity for obese compared with lean participants, although the results might have been confounded by the significant age difference between groups [Geha et al, ]. In a recent study with 496 participants, DMN cohesiveness has been shown to be reduced in young, obese compared with lean individuals, with highest effect size found for the posterior DMN component which is in line with our results.…”
Section: Discussionsupporting
confidence: 92%
“…In our large cohort, we did not observe previously reported increased putamen and insula connectivity [Hogenkamp et al, ], decreased insula–anterior cingulate cortex (ACC) connectivity [Moreno‐Lopez et al, ], increased salience network connectivity [Figley et al, ; Garcia‐Garcia et al, ], reduced temporal lobe network connectivity [Kullmann et al, ] or increased DMN connectivity [Kullmann et al, ; Legget et al, ; Tregellas et al, ] with higher BMI. Similar to our results, one study reported reduced precuneus connectivity for obese compared with lean participants, although the results might have been confounded by the significant age difference between groups [Geha et al, ]. In a recent study with 496 participants, DMN cohesiveness has been shown to be reduced in young, obese compared with lean individuals, with highest effect size found for the posterior DMN component which is in line with our results.…”
Section: Discussionsupporting
confidence: 92%
“…The PFC and amygdala undergo striking structural changes during adolescence (Jalbrzikowski et al, 2017), providing a biological basis that may underlie their unique vulnerability to the disruptive effects of obesity and the consumption of diets rich in saturated fats and sugars. Paralleling clinical data in humans (Geha et al, 2017;Riederer et al, 2016), we showed that DIO rats exhibit significant and partly irreversible microstructural alterations in mPFC regions and amygdalar nuclei associated with fear learning and fear extinction (Vega-Torres et al, 2018). The impact of obesogenic diets on PFC and BLA neuroplasticity is supported by studies showing reduced dendritic spine density in the PFC (Dingess et al, 2017) and dendritic length in the basal arbors of the BLA (Janthakhin et al, 2017) in rats that consume obesogenic diets rich in fats.…”
Section: Short Exposure To An Obesogenic Diet Attenuates Basomedial Asupporting
confidence: 70%
“…The PFC and amygdala undergo striking structural changes during adolescence (Jalbrzikowski et al, 2017), providing a biological basis that may underlie their unique vulnerability to the disruptive effects of obesity and the consumption of diets rich in saturated fats and sugars. Paralleling clinical data in humans (Geha et al, 2017;Riederer et al, 2016), we showed that DIO rats exhibit significant and partly irreversible microstructural alterations in the mPFC and amygdala regions associated with fear learning and fear extinction (Vega-Torres et al, 2018). The impact of obesogenic diets on PFC and BLA neuroplasticity is supported by studies showing reduced dendritic spine density in the PFC (Dingess et al, 2017) and dendritic length in the basal arbors of the BLA (Janthakhin et al, 2017) in rats that consume obesogenic diets rich in fats.…”
Section: Obesogenic Diet Leads To Abnormal Maturation Of the Neural Asupporting
confidence: 69%